Respuesta :

Answer:

Step-by-step explanation:

x= 6± √(6)^2-4(1)(6)   /2(1)

=6± √12   /2

=6± 2√3   /2

=3± √3

Answer:  The required solution of the given quadratic equation is

x = 3 + √3  and  x = 3 - √3.

Step-by-step explanation:  We are given to solve the following quadratic equation using quadratic formula :

[tex]x^2-6x+6=0~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)[/tex]

Quadratic formula :  The solution of a quadratic equation of the form [tex]ax^2+bx+c=0,~a\neq 0[/tex] is given by

[tex]x=\dfrac{-b\pm\sqrt{b^2-4ac}}{2a}[/tex]

For the given quadratic equation (i), we have

a = 1,  b = -6   and   c = 6.

Therefore, the solution of equation (i) is given by

[tex]x\\\\\\=\dfrac{-b\pm\sqrt{b^2-4ac}}{2a}\\\\\\=\dfrac{-(-6)\pm\sqrt{(-6)^2-4\times 1\times6}}{2\times1}\\\\\\=\dfrac{6\pm\sqrt{36-24}}{2}\\\\\\=\dfrac{6\pm\sqrt{12}}{2}\\\\\\=\dfrac{6\pm2\sqrt{3}}{2}\\\\=3\pm\sqrt3.[/tex].

Thus, the required solution of the given quadratic equation is

x = 3 + √3  and  x = 3 - √3.